1994
DOI: 10.3354/meps110019
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation in the coral genus Platygyra: environmental influences and taxonomic implications

Abstract: Scleractinian corals are notoriously variable and the high degrees of morphological variation displayed by some species, particularly in response to environmental influences, confound our understanding of species boundaries. In order to fully understand the ranges of variation and the influence of habitat on colonies within the genus Platygyra, levels of intra-and interspecific morphological variation were quantified and colony morphology was examined relative to environmental gradients. Measurements of 9 skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Miller 1994;Shaish et al 2007;Todd 2008). In some taxa, transplant experiments have demonstrated that colony morphology can largely vary with habitat changes (e.g.…”
Section: Phenotypic Plasticity Versus Genotypic Variation In P Damicmentioning
confidence: 99%
“…Miller 1994;Shaish et al 2007;Todd 2008). In some taxa, transplant experiments have demonstrated that colony morphology can largely vary with habitat changes (e.g.…”
Section: Phenotypic Plasticity Versus Genotypic Variation In P Damicmentioning
confidence: 99%
“…Knowlton et al 1992, 1997, Weil 1993, Van Veghel & Bak 1993, Knowlton & Jackson 1994, Lasker et al 1996, whereas other 'morphological species' are being found to have only small genetic or reproductive differences (e.g. Miller 1994, Szmant et al 1997.…”
Section: Implications Of Plasticity In Coralsmentioning
confidence: 99%
“…Analogous to plants, this variation can be due to genetic differentiation (Willis & Ayre 1985, Ayre & Willis 1988, phenotypic plasticity (Foster 1977, Miller 1994, Bruno & Edmunds 1997, Muko et al 2000 or both in synthesis (Foster 1979, Amaral 1994. As the majority of coral systematics is based upon morphological traits (Brakel 1977, Veron 2000, any plasticity of taxonomically important characters has far-reaching consequences.…”
Section: Introductionmentioning
confidence: 99%
“…While most of these changes take longer than a day, some, such as polyp expansion and contraction, occur within minutes (Levy et al, 2003). Changes in the density of the zooxanthellae and reshuffling of their species occur within days, whereas changes in growth form of the coral colony may take several months to years (Graus and Macintyre, 1982;Miller, 1994;Todd et al, 2004), and genetic selection takes thousands of years (Falkowski et al, 1990).…”
Section: Introductionmentioning
confidence: 99%